Prerequisites for the formation of Neostructuralism as an integral linguistic paradigm - Kravchenko M.A. (Slovo.ru : Baltiĭskiĭ akt͡s︡ent, 2025)
This work is the result of methodological reflection related to the comprehension of more than two hundred years of experience accumulated since the secularization of linguistics, and the formation of a reasonable forecast regarding the near and medium-term development of linguistic science. The development of linguistics is determined by the dynamics of paradigms. In understanding the latter term, the author follows the tradition laid down by Kuhn, taking into account the nuances of its transfer to the linguistic soil formulated by academician Stepanov. The paradigm forms a deep methodological framework that has a direct impact on the goals, subject and methods of research. At the same time, the paradigm shift reflects the development and continuity of linguistic knowledge. The driving force behind the development of linguistics is the competitive struggle between the ideas of anthropocentrism and systemocentrism. To explain the mechanism of paradigmatic cyclicity, the author refers to the concept of the paradigm life cycle. The article demonstrates the signs of "aging" of the current anthropocentric paradigm. Modern linguistics is on the threshold of a new methodological search. At the current moment, prerequisites are emerging for methodological transformations, the result of which may be the creation of an integral (universal) research paradigm capable of providing complete and adequate comprehension of language. Neostructuralism is considered as a variant of the implementation of the integral paradigm, as a linguistic platform that provides a return to the fundamental positions of systemocentrism while preserving the most productive ideas of anthropocentrism. The research principles of neostructuralism encompass holism, taxonomy (emphasis on taxometric approaches), semiotics (focus on the semiotic nature of language), multidimensionality, functionalism, and textocentrism.